O-010 Five-year australian experience with pipeline™ flex embolization devices with shield technology™: real world evidence (SCOPE-AUS). (22nd July 2019) - Rice, H; de Villiers, L; Owusu, M; Wenderoth, J; Chiu, A; Manning, N; Cheung, A; Phillips, T; Rapier, C; Gatty, S; Ninnes, L; Hughes, I; et al.
Abstract : Objective: The Pipeline™ Flex Embolization Device with Shield Technology™ has been available in Australia for 4 years to treat intracranial aneurysms of the anterior and posterior circulation in both elective and ruptured presentations. There is the potential for Shield Technology™ device surface modification to reduce platelet adhesion and platelet specific thrombogenicity. The SCOPE-AUS retrospective multicenter observational cohort study will report risk-adjusted safety and effectiveness outcomes in real-world patient populations treated with the Pipeline™ Flex Embolization Device with Shield Technology at four major centers in Australia. Methods: Real-world outcome analysis of 500 consecutive cases performed between 01 April 2015 - 30 June 2018 at four major centers in Gold Coast, Sydney and Perth will be presented. Pre-defined data variables are collated in a databank of patient socio-demographics, aneurysm and device characteristics, safety and clinical outcomes. Independent neurointerventionist assessments will determine the effectiveness of intracranial aneurysm treatment using validated grading scales to report complete aneurysm occlusion. Safety endpoints will be adjudicated by an independent neurointerventionalist to classify the aetiology of a neurological adverse event. Data abstraction metrics reporting interrater reliability (κ +0.80) and intrarater reliability (ICC 0.75–0.90) will be presented. Results: Comprehensive statistical analysis of the data will report total prevalence, morbidity, mortality and time-to-event analyses at post procedural timepoints (30 days, 6 months and 12 months) using descriptive statistics, Kaplan Meier curves and logistic regression models. Both crude and adjusted estimations of association and risk for confounding or predictive factors in the patient population will be reported. Both relative risk and odds ratios with 95% confidence intervals and p-values will be presented. Conclusion: The findings from this study will present real world safety and efficacy outcomes of high volume centers in Australia using the Pipeline™ Flex Embolization Device incorporating surface modification with Shield Technology™ in contemporary practice. Human Research Ethics approval number HREC/17/QGC/331; clinicaltrial.gov registration NCT03815149 ; Grant funding : Medtronic External Research Program, Medtronic Australasia Pty Ltd, Australia. References: Girdhar G, Li J, Kostousov L, Wainwright J, Chandler WL. In-vitro thrombogenicity assessment of flow diversion and aneurysm bridging devices. Journal of Thrombosis and Thrombolysis 2015;40(4):437–443. doi:10.1007/s11239-015-1228-0 Guidance for Industry and Food and Drug Administration Staff: Use of Real-World Evidence to Support Regulatory Decision-making for Medical Devices. Document No: 1500012. SNIS Abstract SCOPE-AUS 2019 Disclosures: H. Rice: 1; C; Medtronic External Research Program, ISR-2017-10909. 2; C; Medtronic, Stryker. 5; C; Queensland Health, QScan Radiology Clinics. L. de Villiers: 2; C; Medtronic, Stryker. 5; C; Queensland Health, QScan Radiology Clinics. M. Owusu: None. J. Wenderoth: 2; C; Medtronic. 5; C; NSW Health, Sydney Neurointerventionalist Specialists. A. Chiu: None. N. Manning: None. A. Cheung: None. T. Phillips: None. C. Rapier: None. S. Gatty: None. L. Ninnes: None. I. Hughes: None. T. Green: None.